PERSEPSI MASYARAKAT TERHADAP PELAYANAN PERIZINAN ONLINE DI KOTA YOGYAKARTA - , CHARINA V B; , Dr. Rini Rachmawati, M.T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Adoption of information, communication and technology in government (e-Government) including the provision of public services (e-service) is used to interact with the citizen using electronic media such as telephone, fax, email and internet. Yogyakarta has implemented the utilization of website and also provides online licensing service. The use of this service has not been optimal yet. Therefore this study is aimed to describe the online licensing service